EVALUATION OF YIELD SEDIMENT IN FLOW AREA RIVER RIVER PART IN ESTABLISHING THE REST OF DADMA WAREHOUSE - Muhammad Nursa'ban (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2008)
The objective of this research are to: 1). Knowing the level of erosion that happened in the upstream of Cisanggarung Catchments' area. 2). Knowing the level of Sediment Yield in Darma reservoir. 3). Determining the estimation age left Darma reservoir.This is the explorative research. Data collecting was conducted with observation method and documentation. Calculating of total erosion summing factors from surface erosion with dale erosion and channel erosion which level of is 25% from surface land;ground erosion that is using Universal approach [of] Soil Loss Equation ( USLE), while calculation of total erosion that is factor losing of land;ground. Erosion enabled to be to be analysed by conversion each;every land;ground erosion criterion enabled with tables guidance of stipulating of value of T for land;ground in Indonesia, is later;then multiplied 10 and land;ground volume weight. Analyse Sediment Yield [counted/calculated] high [of] water [at] highest terendah level until, river stream debit when different, and high [relation/link] and debit irrigate to adrift sediment ( Load Suspended) and sediment creep ( Bed Load), and also debit [relation/link] irrigate with Sediment Yield. Rest of Accumulating basin of Darma known from sediment amount closing over dead accommodationResult research of menunjukan that surface land;ground erosion storey;level that is 31.558,74 ton / year, or mean 573,795 ton/ha/tahun, total erosion 39.448,43 ton / year or 717,244 enabled land;ground erosion and ton/ha/tahun that is 686,033 ton / year or [about/around] 12,473 ton/ha/tahun. datas [of] menunjukan that surface erosion storey;level and total erosion take place big compared to high enough [of] enabled erosion. annual Sediment Yield [in] Accumulating basin of Darma that is 32.996,419 ton / year or 14.873,660 m3. Accumulating basin of Darma cannot function again that is at the (time) of reaching umur ± 84,25 year. Year 2006 Accumulating basin of Darma have operated during 36 year so that the rest of Accumulating basin of Darma fufilled [by] dead accomodation him by sediment that is ± 48,25 dead accomodation or year will loaded full (of) that is [at] year ± 2054.